Introduction - Hvid, Helge (Nordic Journal of Working Life Studies, 2012)
In December 2009, a group of working life researchers met in Copenhagen to discuss what could be done to restore relationships in this subject area in the Nordic countries. The starting point of our discussions was the recognition that our collaboration had weakened over the last 10–15 years. We decided, therefore, to establish a journal and resume a tradition of organizing a Nordic working life conference, preferably every second year. You are now reading the fourth issue of the journal, and from 25th to 27th of April 2012 the seventh Nordic Working Life Conference was held in Elsinore in Denmark – after a break of 13 years! It was a very successful conference with over 100 papers, the majority of which can be downloaded from http://www.sfi.dk/paper_upload-10624.aspx. The conference confirmed that the Nordic working life research has a special flavor – due to the characteristics of the working life in the Nordic countries and a research tradition that we believe is distinct, given the high relative density of this kind of research in our part of the world. Our strong belief, therefore, is that the conference is worth nurturing, maintaining, and developing (...)